Comparison of Physicochemical Properties of Malaysian Avocado (Persea americana) Fat and Olive Oil (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study examines the physicochemical properties of crude fat extracted from a Malaysian avocado (Persea americana) cultivar, comparing its characteristics with those of commercial olive oil. The primary objective was to explore the unique characteristics of the lipid extracted from Malaysian avocado, particularly its solid state at room temperature (25 °C), a property not typically observed in commercial oils like olive oil, which remains liquid under similar conditions. The avocado fat was extracted using the mechanical press method, yielding 20.71% fat. A comprehensive analysis was conducted on both avocado fat and olive oil to evaluate various parameters, including colour, slip melting point, iodine value, refractive index, free fatty acid content, peroxide value, and p-anisidine value. The results revealed that while the local avocado fat remains solid at room temperature, olive oil is liquid, making avocado fat potentially more suitable for applications requiring stability at ambient temperatures. The major fatty acids identified in the avocado fat were oleic, linoleic, and linolenic acids, whereas olive oil predominantly contained oleic and palmitoleic acids. In terms of triacylglycerol composition, avocado fat was primarily composed of POL, PLL, POO, and PPL, while olive oil predominantly featured OOO, POO, and OOL. These findings not only provide valuable insights into the properties of Malaysian avocado fat but also highlight its potential as a viable alternative to olive oil in food and cosmetic formulations, where a solid fat at room temperature can be beneficial for enhanced stability, texture, and shelf life.
Keywords: Malaysian avocado; Avocado pulp fat; Mechanical press; Olive oil; Characteristics